ANALYSIS OF INFLUENCE OF CAPITAL STRUCTURE, COMPANY SIZE, COMPANY GROWTH AND PROFITABILITY ON CORPORATE VALUE (Sekolah tinggi ilmu ekonomi pemuda, 2020)
This study has a purpose to explain the significance of the effect of capital structure, firm size, company growth, and profitability affect partially or simultaneously on the value of manufacturing companies listed on the IDX. The population in this study were 144 manufacturing companies listed on the Stock Exchange, a sample of 74 companies during the study period namely 2010-2016 using purposive sampling method with predetermined criteria. The data source used in this study is secondary data. Multiple linear regression is the analytical technique used in this study. After testing, the results of the capital structure, company growth, and profitability are obtained simultaneously and have a significant effect on the value of the company. Partially the capital structure has a negative and significant effect on firm size, company growth and profitability have a positive and significant effect on the value of the company.